Stickstoff basierte Flammschutzmittel für das Lasersintern: Optimierung und Analyse der Recyclingfähigkeit (Studienarbeit) - Hücker, Lars

Phosphorhaltige Lasersinter-Materialien mit Flammschutzwirkung: Optimierung und Analyse der Recyclingfähigkeit (Studienarbeit) - Schulz, Maurice

Flowability of polymer powders at elevated temperatures for additive manufacturing - Rüther, Moritz Johannes; Klippstein, Sven Helge; Ponusamy, SathishKumar; Rüther, Torben; Schmid, Hans-Joachim (Powder Technology)
Keywords: General Chemical Engineering

Entwicklung einer Methode zur Integration der Additiven Fertigung in die Serienproduktion am Beispiel des Lasersinterns - Kruse, Anne

Umsetzung einer optimierten Oberflächenschlitzung zur Wirbelstromverlustreduktion auf der Oberfläche eines additiv gefertigten Permanentmagnet-Rotors - Haase, Michael; Bieber, Maximilian; Tasche, Frederik; Schaper, Mirko; Hoyer, Kay-Peter; Ponik, Bernd; Magyar, Balázs (Proceedings of the 19th Rapid.Tech 3D Conference Erfurt, Germany, 9–11 May 2023)

Powder bed fusion of soft-magnetic iron-based alloys with high silicon content - Andreiev, Anatolii; Hoyer, Kay-Peter; Hengsbach, Florian; Haase, Michael; Tasche, Lennart; Duschik, Kristina; Schaper, Mirko (Journal of Materials Processing Technology)
Keywords: Industrial and Manufacturing Engineering; Metals and Alloys; Computer Science Applications; Modeling and Simulation; Ceramics and Composites

Influence of the filler–matrix adhesion and the effects of conditioning on tensile properties of laser-sintered parts built with polyamide–glass bead dry blends - Kletetzka, Ivo; Kosanke, Maren; Meinderink, Dennis; Neßlinger, Vanessa; Grundmeier, Guido; Schmid, Hans-Joachim (Progress in Additive Manufacturing)
In this work, the influence of the filler–matrix adhesion on the tensile properties of laser-sintered parts built with Polyamide 613 filled with glass beads was investigated. For this purpose, dry blends of glass beads with and without organosilane coupling agents and polyamide powder were prepared and processed into tensile specimens on an EOS P396 laser sintering system. The samples were tested both in the dry state and after an accelerated conditioning in a climate chamber. Furthermore, finite element method (FEM) simulations were performed to model the extreme cases of optimum adhesion and no adhesion. By correlating the tensile tests with the simulation results and by analyzing the fracture surfaces, it was shown that the filler–matrix adhesion is sufficient in the dry state but is strongly degraded by conditioning. Even the presence of various organosilane thin films could not prevent a strong deterioration of the filler–matrix adhesion and the associated deterioration of the mechanical properties. Since a comparison with an injection-molded sample of the same polymer filler combination shows identical behavior after conditioning, it is assumed that this problem is not limited to additively manufactured parts.
Keywords: Industrial and Manufacturing Engineering

Influence of the filler matrix adhesion and the effects of conditioning on tensile properties of laser sintered parts built with polyamide glass bead dry blends - Kletetzka, Ivo; Kosanke, Maren; Meinderink, Dennis; Neßlinger, Vanessa; Grundmeier, Guido; Schmid, Hans-Joachim
Abstract In this work, the influence of the filler matrix adhesion on the tensile properties of laser-sintered parts built with Polyamide 613 filled with glass beads was investigated. For this purpose, dry blends of glass beads with and without organosilane coupling agents and polyamide powder were prepared and processed into tensile specimens on an EOS P396. The samples were tested both in the dry state and after an accelerated conditioning in a climate chamber. Furthermore, FEM simulations were performed to model the limiting cases of optimum adhesion and no adhesion. By correlating the tensile tests with the simulation results and by analyzing the fracture surfaces, it was shown that the filler matrix adhesion is sufficient in the dry state but is strongly degraded by conditioning. Even the presence of various organosilane thin films could not prevent a strong deterioration of the filler-matrix adhesion and the associated deterioration of the mechanical properties. Since a comparison with an injection molded sample of the same polymer filler combination shows identical behavior after conditioning, it is assumed that this problem is not limited to additively manufactured parts.

Tensile Testing for Polymer AM - Best Pratice at the DMRC - Kletetzka, Ivo

Influence of a prolonged shelf time on PA12 laser sintering powder and resulting part properties - Klippstein, Sven Helge; Kletetzka, Ivo; Sural, Ilknur; Schmid, Hans-Joachim (The International Journal of Advanced Manufacturing Technology)
In the laser sintering technology, the semi-crystalline polymer material is exposed to elevated temperatures during processing, which leads to serious material ageing for most materials. This has already been investigated intensively by various authors. However, the ageing of the material at ambient temperatures during shelf life has not been the focus so far. The need to analyse the shelf life can be derived from an ecological and economic point of view. This work is focusing on the shelf life of PA2200 (PA12). To reduce the potential influences of powder production fluctuations, two different powder batches stored for 5.5 years and 6.5 years are investigated and compared to a reference powder produced 0.5 years before these investigations. Multiple powder analyses and part characterisations have been performed. A significant yellowing and molecular chain length reduction can be derived from the measurement results. Whereas the influence on mechanical part performance was minor, the parts built with the stored powders are more yellowish. As it is most likely that this is due to the consumption of polyamide stabilisers, it can be assumed that these parts will be subject to significantly faster ageing. Therefore, it is still not recommended to use the stored powders for critical parts or light intense and humid environments.
Keywords: Selective laser sintering; Shelf life; Polyamide 12; powder; PA2200; material ageing

Charakterisierung und Bewertung von flammgeschützten PA12 Pulvermischungen hinsichtlich der Verarbeitbarkeit im Lasersinter-Prozess - Sajadi, Said

Assessing the Impact of the Powder Production Method on Ceramic-filled Polyamide Composites made by Laser Sintering - Kletetzka, Ivo; Neitzel, Fabian; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
Polymer composites represent the industry standard in injection molding for the production of plastic components with increased requirements in terms of heat resistance and stiffness. In the field of laser sintering (LS), these materials are less common so far. In order to extend the available material variety for the LS process, new ceramic-filled Polyamide 613 powders are investigated within the scope of this work. Here, the resulting properties from two different powder production methods are compared. One filled powder is produced by dry blending and the other powder with the same filler and filling ratio is produced by encapsulating the filler particles inside the polymer particles within the dissolution-precipitation process. It was found that encapsulating the filler particles can provide certain benefits for the processability, for example an improved powder flowability or better filler dispersion. However, encapsulating the filler also alters the thermal properties of the precipitated powder.

Compensation of the Shrinkage Behavior Occurring in Cylindrical Components in the FDM Process - Koers, Thorsten; Magyar, Balázs (Macromolecular Symposia)
Fused deposition modeling (FDM) is an additive manufacturing process that can be used to manufacture three-dimensional thermoplastic components layer by layer. One disadvantage of FDM is the shrinkage of the components during the manufacturing process. The filament is molten in the nozzle, deposited layer by layer, and cools down again. During solidification, the filament shrinks inhomogeneously in the x/y/z direction, which leads to distortion of the component geometries. Particularly with higher nominal lengths and complex local geometries, there is a need for optimization with regard to dimensional accuracy. The aim of this paper is to counteract this on the software side with global as well as local shrinkage factors. The expected shrinkage within a layer is predicted with an in-house developed software. The geometric accuracy of the model is verified by experimental investigations on cylindrical test specimens. In these, the so-called clover effect occurs as a result of the shrinkage. The circular shape of the deposited layer is deformed by the distortion in the x–y plane comparable to a clover. Finally, the results are validated by analyzing a demonstrator in the form of a bracket.

Additively manufactured air-cooled lightweight rotor for an automotive electric motor - Bieber, Maximilian; Haase, Michael; Tasche, Frederik; Zibart, Alexander; Ponick, Bernd (2023 IEEE International Electric Machines & Drives Conference (IEMDC))

Investigation of the influence of process parameters on productivity in the LPBF process for the material Inconel 718 - Bödger, Christian; Gnaase, Stefan; Lehnert, Dennis; Tröster, Thomas (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium – An Additive Manufacturing Conference)
The nickel-based alloy Inconel 718, which is used in aerospace technology, poses a great challenge to conventional machining due to its high strain hardening and toughness. Here, the laser powder bed fusion process (LPBF) offers an alternative with potential savings if sufficiently high productivity can be achieved. Based on the parameter study carried out, starting from the SLM Solutions standard parameters for the manufacturing of components, exposure parameters could be developed to realize manufacturing with 120 μm and 150 μm layer thickness, with almost the same geometric accuracy. For this purpose, the process parameters of laser power, focus diameter, hatch distance and scan speed were varied. The negative defocusing of the laser showed a positive effect on the density of the parts, realizing densities ≥ 99.94 %, with high dimensional stability and good mechanical properties. Considering the reduced manufacturing time of up to 61 %, a significant increase in productivity was achieved.

Adaptive Scaling of Components in the Fused Deposition Modeling Process - Moritzer, Elmar; Hecker, Felix (Macromolecular Symposia)
Abstract Currently, the fused deposition modeling (FDM) process is the most common additive manufacturing technology. The principle of the FDM process is the strand wise deposition of molten thermoplastic polymers, by feeding a filament trough a heated nozzle. Due to the strand and layer wise deposition the cooling of the manufactured component is not uniform. This leads to dimensional deviations which may cause the component to be unusable for the desired application. In this paper, a method is described which is based on the shrinkage compensation through the adaption of every single raster line in components manufactured with the FDM process. The shrinkage compensation is based on a model resulting from a DOE which considers the main influencing factors on the shrinkage behavior of raster lines in the FDM process. An in‐house developed software analyzes the component and locally applies the shrinkage compensation with consideration of the boundary conditions, e.g., the position of the raster line in the component and the process parameters. Following, a validation using a simple geometry is conducted to show the effect of the presented adaptive scaling method.
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Investigation of the Deposition Velocity Related Temperature Deviations for High Temperature Materials in the FDM Process - Moritzer, Elmar; Hecker, Felix; Knaup, Felix; Wächter, Julian (Proceedings of the 37th International Conference of the Polymer Processing Society (PPS-37))

Determination and Compensation of the Shrinkage Behavior of Cylindrical Elements in the FDM Process - Koers, Thorsten; Magyar, Balázs (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium 2023)
Fused Deposition Modeling (FDM) is an additive manufacturing process to produce complex thermoplastic geometries layer by layer. The filament is melted in a nozzle, iteratively deposited, and then cools down. Due to the solidification process, the deposited filament strands deviate from their intended position due to shrinkage, resulting in significant geometric deviations in the final part. In terms of dimensional accuracy, there is a need for optimization, especially for local curved geometries in relation to the global part with higher nominal dimensions. The aim of this study is to investigate the size and shape deviations for cylindrical FDM elements and to compensate the expected deformations by using an in-house software with adaptive scaling factors in the x-y plane. Previous studies mainly focus on simple, non-curved objects, this study also considers the influence of curvature and global as well as local deviations on the final part.

Depiction of support structures in technical drawings - Lammers, Stefan; Koers, Thorsten; Magyar, Balázs; Zimmer, Detmar; Lieneke, Tobias (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium 2023)
To ensure uniform documentation of support structure information, a concept is presented that enables a standardized depiction of support structures in technical drawings based on ISO 128-3. To this end, requirements for a uniform depiction are defined and a procedure for drawing entry is presented. The drawing entry should contain all production-relevant support structure information. The standardized documentation of support structure information in technical drawings is intended to ensure a simple, clear and safe exchange of information between business units or different companies along the value chain. As a result a possible drawing entry of support structures was developed. To distinguish between different support structure types, a standardized depiction of geometrical information in a specification field is shown. The specification field gives a detailed description of the support structure type, the geometry as well as the connection to the part and the building platform. Also uncommon support types like lattice structures or CAD based support structures can be implemented. To ensure the usability the depictio is editable and extendable.

Assessing the Impact of the Powder Production Method on Ceramic-filled Polyamide Composites made by Laser Sintering - Kletetzka, Ivo; Neitzel, Fabian; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
Polymer composites represent the industry standard in injection molding for the production of plastic components with increased requirements in terms of heat resistance and stiffness. In the field of laser sintering (LS), these materials are less common so far. In order to extend the available material variety for the LS process, new ceramic-filled Polyamide 613 powders are investigated within the scope of this work. Here, the resulting properties from two different powder production methods are compared. One filled powder is produced by dry blending and the other powder with the same filler and filling ratio is produced by encapsulating the filler particles inside the polymer particles within the dissolution-precipitation process. It was found that encapsulating the filler particles can provide certain benefits for the processability, for example an improved powder flowability or better filler dispersion. However, encapsulating the filler also alters the thermal properties of the precipitated powder.
Keywords: Additive Manufacturing; Laser Sintering; Filled Materials; Composites; Polyamide 613

Halogen-Free Flame Retardant Powder Materials for Laser Sintering: Evaluation and Process Stability Analysis - Neitzel, Fabian; Kletetzka, Ivo; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
The high flammability of components manufactured by laser sintering (LS) using standard polyamide 12 (PA12) powder still severely restricts their use in industries such as electronics, aviation, and transportation. A key factor for the further establishment of LS is the expansion of the material portfolio with, for example, refreshable and halogen-free flame-retardant (FR) powder materials. Accordingly, various halogen-free FRs are investigated in this work and evaluated with respect to their use in LS. First, their decomposition behavior and mode of action are examined. Subsequently, the additives are dry blended with PA12 to investigate properties relevant for LS, such as particle morphology, thermal behavior and melt viscosity. Afterwards, test specimens for UL94 vertical flame-retardancy tests are produced by processing the dry blends on an EOS P3 LS system. Finally, the process stability of the process-aged powder blends is investigated by again examining the thermal behavior and melt viscosity.
Keywords: Additive Manufacturing; Laser Sintering; Flame Retardant; Polyamide 12

Reproducibility in Polymer Laser Sintering - Klippstein, Sven Helge

Innovative Leichtbau- und Kühlungskonzepte für elektrische Maschinen durch additive Fertigung (ILuKadd3D) - Haase, Michael; Tasche, Frederik; Bieber, Maximilian; Zibart, Alexander

Neue Polymerwerkstoffe - Der Schlüssel für die Industrialisierung - Klippstein, Sven Helge

Investigation and Improvement of Processing Parameters of a Copper-Filled Polymer Filament in Fused Filament Fabrication as a Basis for the Fabrication of Low-Porosity Metal Parts - Moritzer, Elmar; Elsner, Christian Lennart (Macromolecular Symposia)

Development of a Procedure for the Assessment of Material Potentials under Consideration of the Weld Seam Quality for Multi-Material Applications in the FDM Process - Moritzer, Elmar; Wächter, Julian (Macromolecular Symposia)

Mit Gestaltungsrichtlinien zum Erfolg - Moritzer, Elmar; Elsner, Christian Lennart (Kunststoffe)

Reactive Direct Bonding of Digital Light Process Components - Moritzer, Elmar; Driediger, Christine (Macromolecular Symposia)

Innovative Werkstoffherstellung für das Polymer Laser Sintern – Teil 2 - Rüther, Moritz Johannes; Klippstein, Sven Helge; Ponusamy, SathishKumar; Jesinghausen, Steffen; Schmid, Hans-Joachim (Werkstoffe)

Innovative Werkstoffherstellung für das Polymer Laser Sintern – Teil 1 - Rüther, Moritz Johannes; Klippstein, Sven Helge; Ponusamy, SathishKumar; Jesinghausen, Steffen; Schmid, Hans-Joachim (Werkstoffe)

Systematic Investigations Concerning Eddy Currents in Additively Manufactured Structures - Haase, Michael; Zimmer, Detmar (Innovative Product Development by Additive Manufacturing 2021)

Powder Spread Process Monitoring in Polymer Laser Sintering and its Influences on Part Properties - Klippstein, Sven Helge; Heiny, Florian; Pashikanti,, Nagaraju; Gessler, Monika; Schmid, Hans-Joachim (JOM - The Journal of The Minerals, Metals & Materials Society (TMS))
Confidence in additive manufacturing technologies is directly related to the predictability of part properties, which is influenced by several factors. To gain confidence, online process monitoring with dedicated and reliable feedback is desirable for every process. In this project, a powder bed monitoring system was developed as a retrofit solution for the EOS P3 laser sintering machines. A high-resolution camera records each layer, which is analyzed by a Region-Based Convolutional Neural Network (Mask R-CNN). Over 2500 images were annotated and classified to train the network in detecting defects in the powder bed at a very high level. Each defect is checked for intersection with exposure areas. To distinguish between acceptable imperfections and critical defects that lead to part rejection, the impact of these imperfections on part properties is investigated.

Powder Spread Flaws in Polymer Laser Sintering and its Influences on Mechanical Performance - Klippstein, Sven Helge; Schmid, Hans-Joachim (Proceedings of the 33nd Annual International Solid Freeform Fabrication Symposium)
By monitoring the recoating process within polymer laser sintering production, it was shown that multiple powder-spread-flaws can be detected. Those groove-like flaws are expected to be the result of agglomerates jamming between the recoater and the last powder layer. This work is analyzing the interaction between powder-spread-flaws and part properties, showing the influence of the recoating process on the performance of laser sintering parts. Therefore, artificial powder-spread-flaws are applied to the build jobs of tensile test specimens which are measured and analyzed regarding the elongation at break, strength and fracture position. For the characteristics of the flaws, the artificial grooves are varied in depth and width. Furthermore, the position of the flaw is changed form mid part to close to surface areas. It was shown, that several flaws are visible at the part surface, resulting in stress concentration and reduced performance. But there are as well parts with flaw-layers, which are not visible after the build process on the part. Those parts can have significantly reduced mechanical properties as well.
Keywords: Selective Sasersintering; Process Monitoring; Powder Spread

Pulver im 3D-Druck - von Mascarabürsten bis zum Interieur eines Mini-Coopers (Vortrag) - Kletetzka, Ivo; Klippstein, Sven Helge (3D-DRUCK HAUTNAH - Der Einfluss einer Zukunftstechnologie auf unser Leben)

Untersuchung und Modellierung der Materialeigenschaften von glaskugelgefüllten, im Lasersinterprozess verarbeiteten Dry-Blends - Hanselle, Felix Paul

Oberflächenmodifikation von Glaskugeln zur Verbesserung der Adhäsion im Lasersinterverfahren - Kosanke, Maren

Potenzialanalyse für die Nutzung additiver Fertigungsverfahren bei einem Büromöbelhersteller und Realisierung eines Beispielbauteils (Studienarbeit) - Henke, Frederic

Einfluss des Lasersinter-Prozesses auf die Recyclingfähigkeit von flammgeschütztem PA12 Pulver - Ostermeier, Jakob

Einfluss der Lagerdauer von PA12- Lasersinterpulver auf die Verarbeitungs- und Bauteileigenschaft - Sural, Ilknur

VALIDATION AND COMPARISON OF FEM-SIMULATION RESULTS OF THE FUSED DEPOSITION MODELING PROCESS UNDER CONSIDERATION OF DIFFERENT MESH RESOLUTIONS - Moritzer, Elmar; Hecker, Felix (Proceedings of the 33rd Annual Freeform Fabrication Symposium)

Effects of spherical fillers on the processability and mechanical properties of PA613 and PP-based LS dry blends - Kletetzka, Ivo; Gawlikowicz, Roland; Schmid, Hans-Joachim (Proceedings of the 33th Annual International Solid Freeform Fabrication Symposium)
In this work, the influences of spherical fillers on the processing properties and the resulting mechanical properties of laser sintered components are investigated. For this purpose, micro glass spheres, hollow glass bubbles and mineral spheres are dry blended to the matrix polymers polyamide 613 and polypropylene with a filling ratio of 20 and 40 vol%. First, relevant properties of the blends, such as powder flowability, thermal behavior and melt viscosity, are investigated. Based on the results, processing parameters are then developed for the LS process and the mechanical properties of the components are investigated. The aim is to be able to tailor the mechanical properties of LS components by adding fillers and thus to create new application areas for additively manufactured components.

Shelf Life of Polyamide 12 (PA2200) Laser Sintering Powder - Kletetzka, Ivo; Klippstein, Sven Helge; Schmid, Hans-Joachim (Proceedings of the 33th Annual International Solid Freeform Fabrication Symposium)

Evaluation of the Ecological Footprint for Parts from AlSi10Mg manufactured by Laser Powder Bed Fusion - Bödger, Christian; Weiss, Christian; Schiefer, Ekkehard; Heussen, Daniel; Haefner, Constantin (Proceedings of the 33rd Annual International Solid Freeform Fabrication Symposium – An Additive Manufacturing Conference)
The manufacturing industry contributes immensely to the global emissions and therefore is a key factor that has to be addressed when a more sustainable production is desired. Laser Powder Bed Fusion (LPBF) is an AM technique that offers the possibility to manufacture metal parts in a more material efficient way due to the layer-by-layer build-up. Nevertheless, the processing chain for parts from LPBF contains additional steps like powder atomization, which also influence the ecological footprint of the production chain. Within this work, a life-cycle model for the production step of parts from AlSi10Mg powder material is developed. The model is supplied with data from the powder atomization up to the production step, either by literature, database or experimental measurements during production. The footprint in terms of CO2 emissions is then analyzed and emission-intense steps are identified. Two manufacturing scenarios are considered to evaluate the sensitivity on the emissions.

INVESTIGATION OF THE PROCESS PARAMETERS AND GEOMETRY DEPENDENT SHRINKAGE BEHAVIOR OF RASTER LINES IN THE FUSED DEPOSITION MODELING PROCESS - Moritzer, Elmar; Hecker, Felix (Proceedings of the 33rd Annual Freeform Fabrication Symposium)

Dreidimensionale Oberflächenanalyse und Topografie-Simulation additiv hergestellter Laser-Sinter Bauteile - Delfs, Patrick
Anwendungen von Laser-Sinter Bauteilen als Sichtteile sind aufgrund der vergleichsweise schlechten Oberflächenqualität sehr begrenzt. In dieser Arbeit werden dreidimensionale Kennwerte benutzt, um die Oberflächenqualität von Laser-Sinter Bauteiloberflächen und die Einflüsse aus unterschiedlichen Bereichen der gesamten Prozesskette zu evaluieren. Beispielsweise wurden objektive Kennwerte, mit deren Hilfe Orangenhaut zu identifizieren ist, und Prozessparameter, die diese deutlich vermindern, gefunden. Mittels Durchführung von haptischen Versuchen wurde das subjektive Empfinden ermittelt und konnten zu objektiven Kennwerten korreliert werden. Eine mikroskopische Betrachtung des flachen Oberflächenwinkels mit verschieden farbigen Pulvern zeigt neue Erkenntnisse zum Anschmelzvorgang von Partikeln an die Schmelze. Zur nachträglichen Glättung von Oberflächen wurden mechanische, chemische und optische Nachbehandlungsmethoden verwendet und deren Potential aufgezeigt. Eine abschließende neuartige Simulation der dreidimensionalen Topografie bildet die Grundlage für ein Programm zur automatischen und funktionsgerechten Orientierung von Bauteilen, welche am Beispiel eines realen Bauteils erfolgreich validiert wurde. Zusammengenommen zeigen die Ergebnisse, dass die richtige Wahl von Bauorientierung und Prozessparametern entscheidend für die Bauteilqualität ist und selbst eine aufwendige Nachbearbeitung eine ungeschickte Wahl derer nur schwerlich ausgleichen kann.
Keywords: Additive Fertigung; Oberflächenqualität; 3D; Topografie; Simulation; PA12; Laser-Sintern; Rauheit

Erarbeitung eines methodischen Vorgehens zur merkmalspezifischen Charakterisierung der Verarbeitungseignung von nicht verstärkten und faserverstärkten Kunststoffen im Fused Deposition Modeling am Beispiel von Polyamid 6 - Schumacher, Christian
Das Fused Deposition Modeling (FDM) ist ein Verfahren zur additiven Fertigung (AF), welches von der Firma Stratasys Ltd. (früher Stratasys Inc.) kommerzialisiert wurde. Heute existieren auch FDM Maschinen anderer Hersteller. Im Gegensatz zu den Maschinen von Stratasys können bei diesen die Prozessparameter frei gewählt werden. Dadurch ist die Verarbeitung herstellerfremder Materialien möglich. Wie in allen AF-Verfahren, werden im FDM bestimmte Anforderungen an die zu verarbeitenden Materialien gestellt. Die Materialien sollten daher speziell für das FDM ausgewählt bzw. entwickelt werden. Die für eine gute Verarbeitbarkeit notwendigen Materialeigenschaften sind aktuell jedoch nicht hinreichend bekannt. Vielmehr sind auch keine Vorgehensweisen bekannt, um die Verarbeitungseignung verschiedener Materialien im FDM zu bewerten. Im Rahmen dieser Arbeit werden daher Vorgehensweisen vorgestellt, um die Verarbeitungseignung thermoplastischer Kunststoffe im FDM anhand bestimmter Merkmale zu bewerten. Die Schweißnahtqualität, der Bauteilverzug und die Gestaltungsfreiheit werden als wichtige Merkmale identifiziert. Unter Beachtung relevanter Einflussgrößen werden je Merkmal Probekörper und Prüfmethoden entwickelt, um merkmalspezifische Kennwerte zu definieren. Dadurch ist der Vergleich unterschiedlicher Materialien, unabhängig von der verwendeten Maschine und der Datenaufbereitung, möglich. Letztendlich werden verschiedene Materialmodifikationen auf Basis von PA 6 erstellt und mit Hilfe der vorgestellten Vorgehensweisen untersucht und bewertet.

Requirements for Processing High-Strength AlZnMgCu Alloys with PBF-LB/M to Achieve Crack-Free and Dense Parts - Heiland, Steffen; Milkereit, Benjamin; Hoyer, Kay-Peter; Zhuravlev, Evgeny; Keßler, Olaf; Schaper, Mirko (Materials)
Processing aluminum alloys employing powder bed fusion of metals (PBF-LB/M) is becoming more attractive for the industry, especially if lightweight applications are needed. Unfortunately, high-strength aluminum alloys such as AA7075 are prone to hot cracking during PBF-LB/M, as well as welding. Both a large solidification range promoted by the alloying elements zinc and copper and a high thermal gradient accompanied with the manufacturing process conditions lead to or favor hot cracking. In the present study, a simple method for modifying the powder surface with titanium carbide nanoparticles (NPs) as a nucleating agent is aimed. The effect on the microstructure with different amounts of the nucleating agent is shown. For the aluminum alloy 7075 with 2.5 ma% titanium carbide nanoparticles, manufactured via PBF-LB/M, crack-free samples with a refined microstructure having no discernible melt pool boundaries and columnar grains are observed. After using a two-step ageing heat treatment, ultimate tensile strengths up to 465 MPa and an 8.9% elongation at break are achieved. Furthermore, it is demonstrated that not all nanoparticles used remain in the melt pool during PBF-LB/M.
Keywords: grain refinement; crack reduction; laser beam melting; aluminum alloy; titanium carbide; nanoparticle; PBF-LB/M

Aus der Forschung in die Anwendung - Materialqualifizierung im Kunststoff Freiformen - Moritzer, Elmar; Hecker, Felix; Hirsch, André (Kunststoffland NRW report)

Einfluss eines beheizten Bauraums auf die Schweißnahtqualität - Moritzer, Elmar; Wächter, Julian (Plastverarbeiter)

Kleine Tropfen, große Wirkung - Moritzer, Elmar; Hecker, Felix; Hirsch, André (Kunststoffe)

Assessment of AlZnMgCu alloy powder modification for crack-free laser powder bed fusion by differential fast scanning calorimetry - Zhuravlev, Evgeny; Milkereit, Benjamin; Yang, Bin; Heiland, Steffen; Vieth, Pascal; Voigt, Markus; Schaper, Mirko; Grundmeier, Guido; Schick, Christoph; Kessler, Olaf (Materials & Design)
Additive manufacturing, e.g. by laser powder bed fusion (LPBF), is very attractive for lightweight constructions, as complex and stress-optimised structures integrating multiple functions can be produced within one process. Unfortunately, high strength AlZnMgCu alloys tend to hot cracking during LPBF and thus have not so far been applicable. In this work the melting and solidification behaviour of AlZnMgCu alloy powder variants with particle surface inoculation was analysed by Differential Fast Scanning Calorimetry. The aim is to establish a method that makes it possible to assess powder modifications in terms of their suitability for LPBF on a laboratory scale requiring only small amounts of powder. Therefore, solidification undercooling is evaluated at cooling rates relevant for LPBF. A method for the temperature correction and normalisation of the DFSC results is proposed. Two ways of powder modification were tested for the powder particles surface inoculation by titanium carbide (TiC) nanoparticles: via wet-chemical deposition and via mechanical mixing. A low undercooling from DFSC correlates with a low number of cracks of LPBF-manufactured cubes. It appears that a reduced undercooling combined with reduced solidification onset scatter indicates the possibility of crack-free LPBF of alloys that otherwise tend to hot cracking.
Keywords: Aluminium alloy 7075; Differential fast scanning calorimetry; Solidification; Undercooling; Additive manufacturing

Mikrostrukturausprägung additiv gefertigter Gitterstrukturen - Sieger, Alexander
Mit Hilfe der additiven Fertigung, insbesondere dem pulverbettbasierten selektiven Laserstrahl-schmelzen (LBM), können hochkomplexe Strukturen endkonturnah hergestellt werden. Die große Designfreiheit ermöglicht, zelluläre Leichtbaustrukturen zu erzeugen, deren mikrostrukturellen und mechanischen Eigenschaften direkt vom generativen Fertigungsverfahren abhängen. Insbesondere im Bereich des Leichtbaus bieten zelluläre Strukturen neue Ansätze zur Verminderung des Energieverbrauchs. Um dieses Potential vollständig ausschöpfen zu können, müssen die Effekte, die zum Versagen der Bauteile mit integrierten Gitterstrukturen führen, quantitativ beschrieben und verstanden werden. Dies ist Voraussetzung für eine sichere Auslegung. Dazu werden im Rahmen der vorliegenden Arbeit die charakteristischen Eigenschaften dieser Strukturen sowie die Einflussgrößen im Aufbauprozess näher beleuchtet. Im Rahmen dieser Dissertation werden numerische und experimentelle Untersuchungen von zwei unterschiedlichen Gitterstrukturtypen aus den Werkstoffen 316L und TiAl6V4 vorgestellt. Beide Werkstoffe werden unter monotoner, einachsiger Belastung getestet. Die parallel dazu durchgeführte digitale Bildkorrelation (DIC) ermöglicht gleichzeitig die detaillierte Analyse der lokalen Dehnungsverteilung während der Verformung. Mikrostrukturelle Eigenschaften und die resultierenden Gittercharakteristika werden mit Hilfe von rasterelektronenmikroskopischen Analysemethoden untersucht. Zudem erfolgt die Entwicklung eines Finite-Elemente- Modells, mit der Anforderung eines möglichst geringen Rechenaufwandes. Ein abschließender Vergleich der realen Dehnungsverteilung mit der FE- Analyse verifiziert das Modell.
Keywords: Additive Fertigung; TiAl6V4; 316L; Gitterstrukturen; L-PBF

Untersuchung der mechanischen Eigenschaften, Hintergründe und weitere Entwicklungen im Kunststoff Freiformen - Moritzer, Elmar; Hecker, Felix (Jahresmagazin Kunststofftechnik)

Konstruktionsrichtlinien in der Produktentwicklung - Lammers, Stefan; Kruse, Anne; Gierse, Jan; Tominski, Johannes; Lindemann, Christian-Friedrich (Mehrzieloptimierte und durchgängig automatisierte Bauteilentwicklung für Additive Fertigungsverfahren im Produktentstehungsprozess)

Low Temperature Laser Sintering on a Standard System: First Attempts and Results with PA12 - Menge, Dennis; Schmid, Hans-Joachim
The laser sintering process has been a well-established AM process for many years. Disadvantages of LS are the low material variety and the thermal damage of the unprocessed material. The low temperature laser sintering attacks at this point and processes powder material at a build chamber temperature lower than the recrystallization temperature. This drastic reduction in temperature results in significantly less thermal damage to the material. This work deals with the low temperature laser sintering of Polyamide 12 (PA12) on a commercial, unmodified laser sintering system to compare it to standard laser sintered PA12 and to create the basis for low temperature laser sintering of high temperature materials on such a system. First results by changing the exposure parameters and by fixing parts on a building platform show a processing of PA12 on an EOS P396 at a build chamber temperature less than 100 °C instead of standard approx. 175 °C.
Keywords: Low Temp LS; Low Temperature Laser Sintering; Polyamid 12

Generating Physically Sound Training Data for Image Recognition of Additively Manufactured Parts - Nickchen, Tobias; Heindorf, Stefan; Engels, Gregor (Proceedings of the IEEE/CVF Winter Conference on Applications of Computer Vision)

Funktionsoptimierte AM-Gestaltung eines E-Rotors - Magerkohl, Sebastian; Zimmer, Detmar; Tasche, Lennart; Schaper, Mirko; Urbanek, Stefan; Ponick, Bernd (antriebstechnik - Zeitschrift für Konstruktion, Entwicklung und Anwendung von Antrieben und Steuerungen)
Die Additive Fertigung bietet ein hohes Maß an Gestaltungsfreiheit und ermöglicht die wirt-schaftliche Nutzung von konventionell schwer zu verarbeitenden Materialien. Diese Merk-male ermöglichen neuartige Lösungsansätze bei Funktionsbauteilen in fast allen Anwen-dungsbereichen. Dieses Potential kann auch im Elektromaschinenbau genutzt werden. Am Bespiel des Rotors einer permanentmagneterregten Synchronmaschine (PMSM) lassen sich die Herausforderungen und Möglichkeiten exemplarisch beschreiben.

Zukunftstechnologie und moderne Antriebe kombiniert: AM in modularen Antriebssystemen - Zimmer, Detmar; Koers, Thorsten; Bührmann, Tobias (Newsletter der Wissenschaftlichen Gesellschaft für Produktentwicklung)

Online Monitoring des Beschichtungsprozesses im Laser Sintern, Systementwicklung und Einflussanalyse - Klippstein, Sven Helge

Influences of Temperature-Dependent Boundary Conditions on Component Properties in Arburg Plastic Freeforming - Moritzer, Elmar; Hecker, Felix; Elsner, Christian Lennart; Hirsch, André (Proceedings of 36th Annual Meeting of Polymer Processing Society (PPS-36))

Investigation of Plastic Freeformed, Open-Pored Structures with Regard to Producibility, Reproducibility and Liquid Permeability - Moritzer, Elmar; Hirsch, André; Dalmer, C.
The Arburg Plastic Freeforming (APF) is an additive manufacturing process which allows the production of three-dimensional thermoplastic components in layers. The components are produced by depositing fine, molten plastic droplets. The main advantage of the APF is the open-parameter control of the associated machine system. Thus, the process parameters can be optimized for individual applications. A special and new application of the APF is the production of interconnecting porous structures. As this is a novel approach with this manufacturing process, the general producibility and reproducibility must first be proven. Therefore, the relevant process parameters with an influence on the open-pored structures are identified. The volume of the individual plastic droplets, the distance between the droplets and the layer thickness are the three decisive influencing factors. With the use of analysis methods, the free spaces created in the structure are described by a uniformly constructed, interconnected pore structure. This means that the pores are interconnected in three dimensions. Reproducibility is evaluated by repeated production and thru the changed conditions during the manufacturing process. In addition, the multiplication and a change of geometry are evaluated in such a way that there is no influence on the pore size. Irregularities when depositing the first layer are caused by unevenness of the building platform. A suitable test arrangement is set up to determine the liquid permeability. A characteristic value is determined to describe the permeability to liquids.

Investigation of Specific FDM Process Parameters to Optimize the Polymer Discharge of Carbon Fiber Reinforced PEEK - Moritzer, Elmar; Wächter, Julian; Elsner, Christian Lennart (Macromolecular Symposia)

Stainless Steel Parts Produced by Fused Deposition Modeling and a Sintering Process Compared to Components Manufactured in Selective Laser Melting - Moritzer, Elmar; Schumacher, Christian (Macromolecular Symposia)

Investigation and Realization of Watertight FDM Structures Made of Ultem 9085 in Pressurized Systems - Moritzer, Elmar; Elsner, Christian Lennart; Wächter, Julian; Knoop, Frederick (79th Annual Technical Conference of the Society of Plastics Engineers (ANTEC))

Investigation of Metal‐Polymer Composites Manufactured by Fused Deposition Modeling with Regard to Process Parameters - Moritzer, Elmar; Elsner, Christian Lennart; Schumacher, Christian (Polymer Composites)

3D-Druck - Eine Technologie als Schlüssel zur Steigerung der Teilhabe - Kruse, Anne; Ott, Manuel; Risse, Lena; Koch, Rainer

Untersuchung von Polymer-Dry-Blends und Bewertung ihrer Verarbeitungseigenschaften für den Lasersinterprozess (Studienarbeit) - Gawlikowicz, Roland

Investigations for the Optimization of Visual and Geometrical Properties of Arburg Plastic Freeforming Components - Moritzer, Elmar; Hecker, Felix; Elsner, Christian Lennart; Hirsch, André (Proceedings: 2021 Annual International Solid Freeform Fabrication Symposium (SFF Symp 2021))
Arburg Plastic Freeforming (APF) is an additive manufacturing process with which three-dimensional, thermoplastic components can be produced layer by layer. Visual and geometrical properties are a major criterion for characterizing the resulting component quality. The aim of this study was to investigate the influences on visual and geometrical properties of APF components depending on process parameters. Initially the focus was on the analysis of the shrinkage behavior of ABS-M30 (Stratasys). On the basis of the results and an existing procedure by the machine manufacturer, an optimized procedure for determining the scaling factors was developed to counteract the shrinkage. With this procedure a higher dimensional accuracy of the components can be achieved. In addition, it was investigated whether an adaption of the form factor based on a mathematical model depending on the component geometry makes sense. The results were transferred into manufacturing guidelines, which allow the user of the APF-technology to optimize process parameters more efficiently.

Comparison of Component Properties and Economic Efficiency of the Arburg Plastic Freeforming and Fused Deposition Modeling - Moritzer, Elmar; Hecker, Felix; Driediger, Christine; Hirsch, André (Proceedings: 2021 Annual International Solid Freeform Fabrication Symposium (SFF Symp 2021))
The additive manufacturing process Fused Deposition Modeling (FDM) is established in the industry for many years. A new, similar process to FDM is the Arburg Plastic Freeforming (APF). The main differences between both processes are the form of the starting material (FDM: Filaments, APF: Conventional granulate) and the material deposition during the layer formation (FDM: Melt strand, APF: fine molten droplets). Since the two processes can be used in similar applications, the aim of this study is to compare both processes in a holistic way. Furthermore, the advantages and disadvantages of the processes are to be highlighted. The systematic comparison between a Stratasys 400mc and the Freeformer 200-3X is divided into the areas of component properties, design limitations and economic efficiency. The material ABS-M30 (Stratasys) is used in both processes. The results show comparable component properties regarding mechanical and optical properties but also differences in design limitations and cost efficiency.

Investigation and Modeling of the Residence Time Dependent Material Degradation in the Arburg Plastic Freeforming - Moritzer, Elmar; Hecker, Felix; Hirsch, André (Proceedings: 2021 Annual International Solid Freeform Fabrication Symposium (SFF Symp 2021))
The Arburg Plastic Freeforming (APF) is an additive manufacturing process with which three-dimensional, thermoplastic components can be produced layer by layer. One disadvantage of the APF is the long residence time of the molten material in the plasticizing unit compared to conventional injection moulding. The dosing volume is emptied very slowly due to only discharging fine plastic droplets. As a result, long residence times can be expected, which can lead to thermal degradation of the material. The aim of this study was to develop a model for calculating the residence time of the material in the APF. The residence time of the material in the thermally critical dosing volume is predicted using software developed in-house. The accuracy of the model could be verified by experimental investigations. Finally, the thermal degradation of the material was investigated by analyzing the correlation to the mechanical properties of tensile strength specimens.

Laser Sintering Design Guidelines for media transmitting Components - Kletetzka, Ivo; Kummert, Christina; Schmid, Hans-Joachim (Proceedings of the 32nd Annual International Solid Freeform Fabrication Symposium)
In automotive and other fields of application media-carrying components often have complex, flow-optimized geometries and are made of plastics for reasons of weight and cost. Therefore, the laser sintering technology is predestinated to manufacture these components as it offers a very high degree of design freedom and good mechanical properties. For industrial applications the long-term properties of the SLS material in contact with liquid media are important and were therefore investigated for PA12, PP and PA613. Hereby, different media such as motor oil or Glysantin based coolant were tested with different temperatures and immersion times of up to 26 weeks. The mechanical properties were tested after immersion and compared to injection molded samples. Furthermore, laser sintering design guidelines for media-carrying components were developed. These guidelines for instance include the minimum wall thickness to ensure media tightness and the removal of powder from channels with a high length to diameter ratio.

Untersuchung der mechanischen und geometrischen Eigenschaften von Bauteilen hergestellt im Fused Deposition Modeling Verfahren - Knoop, Frederick
Im Rahmen dieser Arbeit wird das additive Fertigungsverfahren Fused Deposition Modeling (FDM) hinsichtlich der erzielbaren Bauteilqualität untersucht. Der Fokus liegt auf den mechanischen und geometrischen Eigenschaften für Bauteile aus ABS-M30. Hierzu erfolgt eine grundlegende Eruierung aller Einflussfaktoren auf die Bauteilqualität. Die Einflussfaktoren, die von besonderer Bedeutung sind, werden mithilfe von experimentellen Untersuchungen genauer analysiert. Ein wichtiges Merkmal im FDM-Prozess ist die Temperatur und die Luftströmung im Bauraum der Fertigungsmaschine, sodass neben der Ermittlung des Istzustandes auch eine Optimierung dieser erarbeitet wird. In den weiteren Hauptkapiteln wird neben dem Einfluss der Temperatur und Luftströmung auch der Einfluss der Strangablagestrategie untersucht. Die Strangablagestrategie kann zu einer gezielten Verbesserung der mechanischen Eigenschaften von FDM-Bauteilen genutzt werden. Die Einflüsse der Strangablagestrategie auf die geometrischen Bauteileigenschaften werden in Form von Maß- und Formabweichungen ermittelt. Ein weiteres Ziel dieser Arbeit ist die grundlegende Analyse über die Ursache von Maßabweichungen an FDM-Probekörpern. Zur Reduzierung der auftretenden Maßabweichungen, wird eine Methode erarbeitet, die zur Bestimmung von optimierten Schwindungsfaktoren dient. Die optimierten Schwindungsfaktoren werden genutzt, um die Maßabweichungen an FDM-Bauteilen maßgeblich zu reduzieren.

Oberflächennachbehandlung beim Fused Deposition Modeling – Analyse der Oberflächenstruktur und mechanischer Kennwerte - Fischer, Matthias
Mit seiner Eignung für den Einsatz in Luftfahrzeugen stellt vor allem der Werkstoff Ultem 9085 in Verbindung mit der Verarbeitbarkeit im Fused Deposition Modeling (FDM) Prozesses ein großes Potential für die Kleinserienfertigung mittels additiver Fertigungstechnologien im Luftfahrtbereich dar. Hier bestehen aufgrund der Schichtbauweise Herausforderungen zur Optimierung der Oberflächenqualität. Des Weiteren ist das Ermüdungsverhalten von FDM-Strukturen noch unzureichend erforscht. Mit dem Schwerpunkt auf dem Werkstoff Ultem 9085 sind im Rahmen dieser Dissertation zunächst Nachbehandlungsmethoden zur Verbesserung der Oberflächenqualität analysiert worden. Hier konnten Oberflächenrauheiten durch den Einsatz eines chemischen Nachbehandlungsprozesses um bis zu 80 % reduziert werden. Die dabei als Nebeneffekt erzeugte Schließung der porösen Oberflächenstruktur begünstigte zudem einen anschließenden Metallisierungsprozess zur Veredelung der Oberflächenstruktur. Die Ermüdungseigenschaften fallen für FDM-Strukturen aufgrund der inneren und äußeren Kerben im Vergleich zu spritzgegossenen Substraten vergleichsweise gering aus. Durch Überfüllung der Bau-teile und gezielte Strangorientierungen kann die Lebensdauer insbesondere für seitlich und flach aufgebaute Zugprüfkörper erhöht werden. Der chemische Nachbehandlungsprozess wirkt sich durch die Reduzierung von äußeren Kerben vor allem positiv auf die mechanischen Eigenschaften von aufrecht hergestellten Strukturen aus.

Additive Leichtbaustrukturen für die Flugzeugkabine - Menge, Dennis; Klippstein, Sven Helge; Schmid, Hans-Joachim

From filament production to material qualification for the FDM process - Moritzer, Elmar; Wächter, Julian

Kombination und Integration etablierter Technologien mit additiven Fertigungsverfahren - Lieneke, Tobias; Künneke, Thomas; Eschner, Niclas; Jacob, Alexander; Schäfer, Martin; Hickmann, Thorsten; Faroun, Rami; Hoffmann, Markus; Scholl, Markus; Baumeister, Kai; Zimmer, Detmar; Lanza, Gisela

Parameter- und Prozessoptimierung für den additiven Fertigungsprozess im Pulverbett am Beispiel der Legierung Ti6Al4V - Ahlers, Dominik
Die additive Fertigung mittels Laser Powderbed Fusion Verfahren (L-PBF) von Metallen wird zunehmend genutzt, um Funktionsbauteile endkonturnah zu fertigen. Die in der vor-liegenden Arbeit untersuchte Parameter- und Prozessoptimierung liefert einen Beitrag zur wirtschaftlichen Nutzung des L-PBF und zeigt, dass höhere Aufbauraten bei der ganzheit-lichen Betrachtung des Prozesses realisierbar sind. Die Parameter- und Prozessoptimierung erfordert eine Untersuchung des Einflusses der Fertigungs- und Nachbearbeitungsparameter auf das erzeugte Volumen sowie auf die Mikrostruktur und die resultierenden Materialeigenschaften. Das Ziel der vorliegenden Arbeit ist die Entwicklung einer optimierten Prozessführung mit abschließender Bewer-tung der Wirtschaftlichkeit. Mit dem entwickelten Gesamtprozess wird eine um den Faktor 1,6 höhere Aufbaurate erzielt. Des Weiteren wird die Methodik zur Erarbeitung des opti-mierten Prozessfensters beschrieben, sodass die Herangehensweise auf weitere Werk-stoffe angewendet werden kann. Die mechanischen Eigenschaften werden für den stati-schen und dynamischen Lastfall untersucht und mit der Mikrostruktur korreliert. Abschlie-ßend wird die Prozessoptimierung zur Fertigung eines Demonstrators eingesetzt und wirtschaftlich validiert. Die Ergebnisse zeigen, dass durch das hier angewendete Vorge-hen eine Prozesszeitreduktion von 22,5% und eine Kostenreduktion von 11% realisiert werden kann.
Keywords: Additive Manufacturing; SLM

Opportunities of 3D Machine Learning for Manufacturability Analysis and Component Recognition in the Additive Manufacturing Process Chain - Nickchen, Tobias; Engels, Gregor; Lohn, Johannes (Industrializing Additive Manufacturing)

Strukturoptimierung einer Messradkomponente zur realitätsnäheren Erfassung von Fahrzeuglastdaten und Bruchmechanische Bewertung - Brüggemann, J.P.; Risse, L.; Woodcock, S.C.; Joy, T.D.; Neumann, J.; Vidner , J.; Kullmer, G.; Richard, H.A. (DVM-Bericht 252, Arbeitskreis: Bruchmechanische Werkstoff- und Bauteilbewertung: Beanspruchungsanalyse, Prüfmethoden und Anwendungen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Einsatz von Topologieoptimierungssoftware - Der Ersatz für den Ingenieur? - Brüggemann, J.P.; Risse, L.; Woodcock, S.C.; Kullmer, G.; Richard, H.A. (DVM-Bericht 405, Arbeitskreis: Additiv gefertigte Bauteile und Strukturen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Implementierung additiver Fertigungsverfahren in den chirurgischen Arbeitsablauf - Risse, L.; Kullmer, G. (DVM-Bericht 405, Arbeitskreis: Additiv gefertigte Bauteile und Strukturen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Influence of Part Microstructure on Mechanicl Properties of PA6X Laser Sintered Specimens - Kummert, Christina; Diekmann, Wolfgang; Tews, Katrin; Schmid, Hans-Joachim (29th Annual International Solid Freeform Fabrication Symposium)

Reduction of systematic measurement deviation in acoustic absorption measurement systems - Claes, Leander; Baumhögger, Elmar; Rüther, Torben; Gierse, Jan; Tröster, Thomas; Henning, Bernd (Fortschritte der Akustik - DAGA 2020)

Prozessbasierte Technologieintegration der Additiven Fertigung in Unternehmen - Rohde, Johannes
Die Additiven Fertigungsverfahren stehen im Übergang zur stärken industriellen Anwendung. Weit mehr als die Hälfte aller mittelständischen Unternehmen sehen die Technologien zukünftig als etablierte Verfahren oder gar Schlüsseltechnologien im eigenen Unter-nehmen. Dass der Schritt zur industriellen Nutzung bislang allerdings nicht erfolgt ist, liegt oft am Prozess der Technologieintegration selbst. Unternehmen gelingt es nicht, die fehlende Expertise aufzubauen, die Akzeptanz gegenüber der Additiven Fertigung erfolg-reich zu stärken und die hohen Kosten zu beherrschen. Diese Problematik bestätigen neben Studien des Industriearbeitskreises Light Alliance und der National Association of Manufacturers (USA) auch der Richtungswandel der Forschungsförderung des Bundesministeriums für Bildung und Forschung. Vor diesem Hintergrund gilt es, die auftretenden Hindernisse der Technologieintegration differenziert zu betrachten und erforderliche spezifische Lösungsmethoden in einzelnen Handlungsfeldern abzuleiten. Für diese Handlungsfelder sind anschließend Vorgehensmodelle zu entwickeln, wodurch Hemmnisse wie die hohen Kosten gelöst werden sollen. Die resultierenden Modelle sind in eine Gesamtsystematik zu überführen, welche Unternehmen unter Berücksichtigung der bestehenden Unternehmensprozesse und -strukturen bei der prozessbasierten Technologieintegration der Additiven Fertigung im Unternehmen unterstützt. Die Anwendbarkeit des Verfahrens wird durch eine industrielle Fallstudie untermauert und validiert.

On the Influence of Thermal Histories within Part Cakes on the Polymer Laser Sintering Process - Josupeit, Stefan
Polymer Laser Sintering (LS) is one of the most used Additive Manufacturing (AM) technologies for the tool-less production of polymer parts. The raw material is a polymer powder which is melted layerwise by the use of laser energy. Especially for the production of single parts, small series, individualized and complex structures, the technology is yet established in few branches. However, inhomogeneous and hardly controllable thermal effects during manufacturing limit the build reproducibility. The present work focuses on temperatures within so-called part cakes, their time dependency and their influence on process quality. Therefore, a temperature measurement system is implemented into a commercial laser sintering machine. Based on the experimental data a model to simulate heat transfer within part cakes is set up. Individual thermal histories during processing are successfully correlated with position dependent powder ageing effects. Another focus is on the analysis of a recycling optimized material. First results of correlations between thermal histories and part properties are shown in order to provide an outlook to further research. The data and knowledge gained through this work can be used to understand thermal effects in greater depth and to increase the process quality via optimizations.
Keywords: Additive Manufacturing; Polymer Laser Sintering; Polymer Science

Zum Laserstrahlschmelzen neuer Kunststoffmaterialien - Lohn, Johannes
Stand der Technik beim Lasersintern von Kunststoffen (SLS) ist die Fertigung von Prototypen aus z.B. Polyamid 12. Die industrielle Serienproduktion mittels SLS erfordert die Qualifizierung von produktspezifischen Materialien. Kernthema dieser Arbeit ist die Verarbeitung von neuen Kunststoffen. Hierzu wird eine optimierte Anlagentechnik entwickelt. Die Verarbeitung von schlecht rieselfähigen Pulvern wird durch ein innovatives Beschichtungssystem ermöglicht. Durch eine zwölf Zonen Heizungsregelung erfolgt die Pulvervorwärmung in der erforderlichen Präzision. Zudem ermöglicht ein variabler Laserspot eine Belichtung mit hoher Detailauflösung bei gleichzeitig hoher Aufbaurate. Der Energieeintrag im SLS Prozess und die Belichtung mit variablem Laserspotdurchmesser werden theoretisch betrachtet und mittels Computertomographie experimentell untersucht. Abschließend wird eine Systematik zur Identifizierung von Prozessparameter für die Verarbeitung neuer Materialien erarbeitet und exemplarisch wird das neue Material Polyamid 613 prozessiert.
Keywords: Additive Fertigung; Selektives Lasersintern; Kunststoff; Energieeintrag

Systematik zum präventiven Schutz vor Produktpiraterie durch Additive Fertigungsverfahren - Jahnke, Ulrich
Produktpiraterie und damit einhergehende Imitationen gefährden neben dem wirtschaftlichen Erfolg der Unternehmen am Beispiel des deutschen Maschinen- und Anlagenbaus auch den sicheren Betrieb von Anlagen und somit von Leib und Leben. Im Kontext der Produktpiraterie werden Additive Fertigungsverfahren durch den global möglichen, nahezu unkontrollierbaren Datenaustausch häufig als Treibertechnologie dargestellt. Dem entgegenstehend werden die Additiven Fertigungsverfahren aber in der Literatur auch sehr undifferenziert als mögliche Produktschutzmaßnahme aufgeführt. Darauf deuten auch die Ergebnisse einer Studie des Verbands Deutscher Maschinen- und Anlagenbau e.V., der auf das Reverse Engineering als relevanteste Informationsquelle für Imitatoren verweist. Vor diesem Hintergrund gilt es, die Motivation und das Vorgehen der Imitatoren zu untersuchen und den technischen und wirtschaftlichen Potentialen der Additiven Fertigungsverfahren differenziert gegenüberzustellen. Darauf aufbauend ist ein systematisches Vorgehen zum präventiven Produktschutz durch Additive Fertigungsverfahren zu entwickeln. Die resultierende Systematik führt die Unternehmen unter Berücksichtigung des präventiven Produktschutzes schrittweise durch die Produktentstehung und unterstützt bei der Identifikation schützenswerter Funktionen sowie der Auswahl und Implementierung geeigneter additiver Schutzpotentiale. Die Anwendbarkeit des Verfahrens wird durch eine industrielle Fallstudie untermauert und validiert.

Intelligente Optimierung von Produktgeometrien für die additive Fertigung - Reiher, Thomas
Die additive Fertigung als werkzeugloses Fertigungsverfahren bietet zahlreiche neue Möglichkeiten in der technischen Produktgestaltung. Insbesondere auf Leichtbau optimierte, hochkomplexe Strukturen lassen sich hiermit wirtschaftlich fertigen. Die Bauteile müssen jedoch auch speziell auf die Verfahren angepasst sein, um sicher, fehlerfrei und kostengünstig produziert werden zu können. Mit konventionellen Konstruktionsverfahren sind solche Strukturen nur schwer erzeugbar. Im Rahmen dieser Arbeit wird daher eine Methodik zur intelligenten Optimierung von Produktgeometrien, angepasst an die additive Fertigung, entwickelt. Dies beinhaltet die automatische Erzeugung von anwendungsfallspezifisch optimierten Geometrien sowie deren Überführung in Datenstrukturen, welche in konventionellen CAD-Systemen nutzbar sind. Als grundlegendes Werkzeug wird dabei die Topologieoptimierung verwendet, welche hochaufgelöst durchgeführt und im Anschluss mit hoher Qualität geglättet und weiterverarbeitet werden muss. Hierzu wurde ein durchgängiger voxelbasierter Ansatz gefunden, der auch die Anpassung der Geometrien an die additive Fertigung erlaubt. Die Entwicklung und Funktionalität des Ansatzes wird auf Basis mehrerer Beispielbauteile gezeigt. Das Ergebnis der Optimierungen sind hochkomplexe, im Detail optimierte und an die additive Fertigung angepasste Strukturen.

Entwicklung einer Entscheidungsunterstützung für den Einsatz Additiver Fertigung in der zeitkritischen Ersatzteilversorgung - Deppe, Gereon
Industrieunternehmen versuchen zunehmend das technologische und ökonomische Potential des schichtbasierten Fertigungsansatzes der additiven Fertigung vorteilhaft für sich einzusetzen. Problematisch ist dabei jedoch die geringe Erfahrung der Unternehmen mit der additiven Fertigung und ihren Besonderheiten. Ein Vergleich mit anderen Fertigungsverfahren muss dabei über eine reine Kostenkalkulation hinausgehen, um zusätzliche Potentiale und Einschränkungen abwägen zu können. Die vorliegende Arbeit gibt daher einen Überblick über die wesentlichen Einflussfaktoren Kosten, Zeit und Qualität und es wird auf dieser Basis eine Entscheidungsunterstützung entwickelt, die bei der Identifizierung vorteilhafter Einsatzmöglichkeiten für die additive Fertigung hilft. Da die additive Technologie auch signifikante Änderungen im Bereich der Supply Chain erzielen kann, liegt der Fokus des Einsatzgebietes auf der zeitkritischen Ersatzteilversorgung, betrachtet am Beispiel der Luftfahrtindustrie. In diesem Kontext ist es Ziel und Zweck der Arbeit, die oftmals isoliert betrachteten drei Bereiche Kosten, Zeit und Qualität zu einem ganzheitlichen Vergleich zu kombinieren. Die entwickelte Entscheidungsunterstützung ist dabei auf Basis einer funktionserweiterten Tabellenkalkulation als Demonstrator umgesetzt worden.

FVA-Nr. 813 I - Generative Verfahren zur Herstellung von Polymerbauteilen - Menge, Dennis; Walter, Rolf; Schmid, Hans-Joachim; Breuer, Ulf Paul

Mikrostrukturelle und mechanische Eigenschaften der im Laserschmelzverfahren verarbeiteten Inconel 718 Nickelbasis-Superlegierung - Aydinöz, Mehmet Esat
Im Rahmen dieser Arbeit wurden die mikrostrukturelle Entwicklung und die daraus resultierenden mechanischen Eigenschaften der im SLM® Verfahren (Selective Laser Melting) verarbeiteten Nickelbasis-Superlegierung Inconel 718 untersucht. Anschließend wurde der Einfluss des HIP-Prozesses (Heißisostatisches Pressen) auf die Porosität, die Mikrostruktur und die mechanischen Eigenschaften analysiert. Da der HIP-Prozess oberflächennahe Poren nicht schließen kann, wurden ausgewählte Proben durch das Arc-PVD-Verfahren (Physical Vapor Deposition) mit einer Ni-20Cr Beschichtung gekapselt. Da die typischen Zellstrukturen zusammen mit den γ´´- Ausscheidungen nach dem Lösungsglühen mit anschließender Ausscheidungshärtung auftreten, konnte die höchste Streckgrenze (Rp0,2) unter quasistatischer Belastung bei Raumtemperatur (RT) sowie bei 650 °C ermittelt werden. Unter zyklischer Belastung zeigen die beschichteten und heißisostatisch gepressten Proben die geringste Ermüdungsfestigkeit bei RT, sowohl vor als auch nach der Ausscheidungshärtung. Im lösungsgeglühten und anschließend ausscheidungsgehärteten Zustand weist das Material die höchste Lebensdauer, insbesondere bei einer niedrigen Dehnungsamplitude (Δε/2 = ±0,35 %), bei 650 °C auf.
Keywords: Additive Fertigung; Laserschmelzverfahren; Nickelbasis-Superlegierung; Inconel 718; Mikrostruktur; mechanische Eigenschaften; Heißisostatisches Pressen; Beschichtung

Schlussbericht zum Vorhaben "Additive Leichtbaustrukturen für Flugzeugkomponenten" : Verbund: KOBFS - Kostenoptimierter Baukasten für Flügelsysteme - Ahlers, Dominik; Tröster, Thomas

Entwicklung von Optimierungsstrategien für Strukturbauteile unter Ausnutzung der Potentiale des Laser-Strahlschmelzens - Brüggemann, J.P.; Risse, L.; Kullmer, G.; Richard, H.A. (Additive Fertigung von Bauteilen und Strukturen – Neue Erkenntnisse und Praxisbeispiele)

Einsatz ingenieurmäßiger Methoden zur Lösung chirurgischer Herausforderungen - Risse, L.; Woodcock, S.C.; Kullmer, G.; Schramm, B.; Richard, H.A.

Möglichkeiten additiver Fertigungsverfahren im Zuge der Digitalisierung für den Planungsprozess chirurgischer Eingriffe - Risse, L.; Schramm, B. (DVM - Bericht 1685, DVM-Tag 2019 – Bauteil verstehen)

Einflussfaktoren auf Bauteilgüte lasergeschmolzener Strukturen - Brüggemann, J.P.; Risse, L.; Richard, H.A.; Kullmer, G. (DVM - Bericht 251, Arbeitskreis: Bruchmechanische Werkstoff- und Bauteilbewertung: Beanspruchungsanalyse, Prüfmethoden und Anwendungen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Bewertung von verschieden gearteten Gitterstrukturen in Bezug auf ihre Einsatzfähigkeit in Bandscheibenimplantaten - Woodcock, S.C.; Risse, L.; Kullmer, G.; Richard, H.A. (DVM - Bericht 404, Arbeitskreis: Additiv gefertigte Bauteile und Strukturen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Einflussfaktoren auf Bauteilgüte lasergeschmolzener Strukturen - Brüggemann, J.P.; Risse, L.; Richard, H.A.; Kullmer, G. (DVM-Bericht 251, Arbeitskreis: Bruchmechanische Werkstoff- und Bauteilbewertung: Beanspruchungsanalyse, Prüfmethoden und Anwendungen, Deutscher Verband für Materialforschung und -prüfung e.V.)

Potentiale des Einsatzes individueller, additiv gefertigter medizinischer Hilfsmittel - Risse, L.; Woodcock, S.C.; Kullmer, G.; Schramm, B.; Schlenker, F.; Richard, H.A. (DVM-Bericht 404, Arbeitskreis: Additiv gefertigte Bauteile und Strukturen)

Strukturoptimierung durch den Einsatz des Laser-Strahlschmelzprozesses zur realitätsnäheren Erfassung von Fahrzeug-Lastdaten - Brüggemann, J.P.; Risse, L.; Woodcock, S.C.; Duffe, T.; Neumann, J.; Vidner, J.; Kullmer, G.; Richard, H.A. (DVM-Bericht 404, Arbeitskreis: Additiv gefertigte Bauteile und Strukturen, Deutscher Verband für Materialforschung und -prüfung e.V.)